Are Polish Hospital Pharmacies Ready for Changes in Drug Distribution? - Karolina Ewa Wylegała; Marcin Czech; Urszula Religioni; Dariusz Stencel (Polskie Towarzystwo Farmaceutyczne, 2024)
All tasks performed by hospital pharmacies concern the management of medicinal products. The aim of this work is to analyze the functioning and implemen-tation costs of unit-dose and multi-dose automatic drug distribution systems in comparison with the classical mode of so-called ward medicine cabinets. The study was conducted from January 2020 to October 2021. It included quantitative study, conducted to verify the functioning of hospital phar-macies based on an original questionnaire, which was completed by 26 masters of pharmacy em-ployed in pharmacies hospitals, of which 92.4% were pharmacy head, and in-depth face-to-face interviews conducted in 4 facilities with unit-dose systems and one center that uses the multi-dose system. The work presents the functioning of hospital pharmacies, and the advantages and disadvantages of classical distri-bution model. Opinions on the operation of unit-dose and multi-dose systems as well as experiences related to their implementation in the hospital, including the necessary changes in the structure and organization of the hospital, were also presented. In conclusion, despite high purchase costs, auto-mated drug distribution systems bring many benefits in the field of hospital functioning, mainly in relation to patient care, improving the effectiveness, safety and individualization of pharmacothera-py. The main barriers to implementation of these systems are high costs, lack of IT infrastructure adaptation, the need to change the organization of staff work and the lack of factory-prepared col-lective packaging. In the opinion of pharmacists, changes in the distribution of drugs are necessary and beneficial from proper pharmacotherapy perspective.